Interplay of two signals in a neuron with heterogeneous synaptic short-term plasticity - Droste, Felix; Schwalger, Tilo; Lindner, Benjamin (Frontiers in Computational Neuroscience, 2013)
Signals from different sensory modalities may converge on a single neuron. We study theoretically a setup in which one signal is transmitted via facilitating synapses (F signal) and another via depressing synapses (D signal). When both signals are present, the postsynaptic cell preferentially encodes information about slow components of the F signal and fast components of the D signal, whereas for a single signal, transmission is broadband. We also show that, in the fluctuation-driven regime, the rate of information transmission may be increased through stochastic resonance. Remarkably, the role of the beneficial noise is played by another signal, which is itself represented in the spike train of the postsynaptic cell.